ANALISIS PEMBERIAN KREDIT, PENDAPATAN BUNGA BERSIH DAN DANA PIHAK KETIGA TERHADAP LABA PADA BANK BUMN - Marwansyah, Sofyan; A. Sudrajat, A. Sudrajat (Aksara Public, 2018)
A Bank as a means of intermediation in the world economy today is growing day by day, one of the bank's function is to collect funds from third parties and redistribute in the form of Credit, where in this activity the bank get interest income so that bank has profit in the form of profit earned. in this research the authors want to know the relationship and influence either partially or stimultaneously between third party funds, lending, and interest income to Earnings of State Banks period 2007 to 2016 where the data authors take from the data summary financial statements listed on the website idx. The method used in this study using multiple linear regresion analysis with the first step to test the classical assumptions first processed using SPSS software version 21, the results obtained that partial lending has an influence of 45.2% on earnings, Interest Revenues by Partial has an influence of 41.4% on Profit, Third Party Funds partially have the effect of 72.2% On Profit, while credit, Interest Income and Third Party Funds Simultaneously have the effect of 93.3% of Profit.